Pendidikan, Pelatihan (DIKLAT) dan Pengembangan Pegawai untuk Meningkatkan Kinerja Pegawai - Regen, Ronal; Helia, Suhelmi; Marlius, Doni; Dona, Elva; Fernos, Jhon (Majalah Ilmiah UPI YPTK, 2024)
Education and development is one of the efforts that can be made by organizations in order to improve the education, skills, competencies and performance of their employees, therefore education and training (training) for an organization must be seen as a long-term investment in the field of human resources. Civil servants as state apparatus are required to provide good service to the community, to maintain the survival of an agency it needs to be supported by human resources who have a leadership spirit, have skills, have high creativity. The quality of work of civil servants (PNS) is considered inadequate and is below the expected quality standards, such as slow service delivery to the general public, lack of coordination of several jobs, lack of respect for working hours, discipline and working time, all of which indicate that the quality of civil servants (PNS) needs to be addressed. Qualified, highly motivated human resources who are willing to work together in teams will be the key to organizational success. The objectives of this community service activity are to provide education, training and employee development to improve the quality of public services, develop managerial capacity, strengthen ethics and morality, and improve employee leadership. Participants who participated in this community service activity amounted to 50 people. The material presented is about education, training (DIKLAT) and employee development to improve employee performance. The results of the training show that employees have an understanding of education, training and development to improve employee performance. This activity is expected to be able to improve employee performance so that services to the community also improve.